PERFORMANCE OPTIMIZATION OF BEAM CONCRETE BEAMS TO INCREASE BUILDING STRUCTURE PERFORMANCE IN EARTHQUAKE AREA - Agus Santoso; Slamet Widodo; Nuryadin Eko Raharjo (Jurnal Penelitian Saintek, 2010)
The paper  summarizes  the experimental  result of flexural  capacity of full scale reinforced concrete beam prepared  as a composite  members consisting  of two concrete layers  made of Hybrid Fiber Reinforced  Concrete (HFRC) and High Strength Concrete (HSC). Compressive  strength and modulus of elasticity test, splitting tensile, flexural  tensile tests conducted  to identify the important mechanical properties of both HFRC and HSC. Every mechanical properties data collected using 3 standard samples based on ASTM and SNI codes. 15 reinforced concrete beams in 150x250x2400 mm dimensions,  usedfor full  scale flexural   test of structural  RC beam.  The tests conducted  on 5 types of composite  beam: 100%, 75%, 50%, 25%, and 0% of HSC cross sectional depth, combined with HFRC for the opposite sides.The experimental results indicated that HFRC shows higher modulus elasticity compared with HSC, it was 28618,611MPafor  HFRC,  and 21790,660 MPafor HSC. All types of composite  members  and full   depth  of HFRC  shows  higher first   crack  load  capacity compared  with HSC structural reinforced  concrete  beam. The first  crack  load capacity increase ranging from 29,753%  up to 33,267%. All types of composite  members and full depth of HFRC also shows higher maximum load capacity compared with HSC structural reinforced concrete beam. The first  crack load capacity  increase ranging from  11,284% up to 16,03%. Based on the experimental  test results, it can be suggested  to apply partial depth of HSC and HFRC; 50% HSC and 50% HFRC on static determinate  RC beam.Keywords:  Composite Reinforced Concrete Beam, HFRC, HSC, Full Scale Flexural  Test